Root Border Cells as a Convenient Single Cell System to Study Plant-Environmental Interactions: A Case Study for Aluminum Tolerance - Feng, Yingming; Chen, Xingyun; Li, Xuewen; Li, Yalin; Nong, Wei; Tang, Jiao; Han, Hongxiang; Shi, Lei; Shabala, Sergey; Yu, Min (Frontiers in Soil Science, 2022)
Root border cells (RBCs) are a group of cells that originated from the root cap meristem, which are developed by genetic regulation and play a variety of biological functions. Being composed of a homologous single cell population with high metabolic activity and intact cell walls, RBCs represent a highly useful tool for studying various aspects of plant mineral absorption and utilization, as well as plant-soil-microbiome interactions in the rhizosphere. Research on RBCs also promise to become a hotspot in the context of understanding root adaptive responses to hostile environments. In order to take advantage of RBCs as an ideal single cell system in plant-environmental interactions, we summarized the production and function of RBCs and built-up the methodology for RBCs culturing, purification, and quantity control for plant research. The latter is done by using a case study of the application of RBCs to study mechanisms of Al toxicity in plants. This work offers plant scientists a new cognition of adopting RBCs as a convenient single cell system for the multidisciplinary research including (but not limited to) plant physiology, development and genetics, nutrition, and stress and adaptation. Root border cells (RBCs) are derived from the root cap and represent a population of living cells with special physiological activity and biological roles that are different from the root cap cells per se. After being separated from the root cap, RBCs become more active in metabolism than the progenitor root cap cells; for example, they incorporate labeled amino acids into protein 2.6-fold more efficiently than the cells of the root cap. In addition, mRNA and protein were differentially expressed between root cap cells and RBCs. Since the production of RBCs is genetically regulated and RBCs played a variety of biological functions in resistance to biotic and abiotic stresses occurred in the rhizosphere, RBCs were suggested as an ideal single cell system for the study the response of plant root cells to nutrient availability, environmental stresses, and in plant-microbial interactions. Some studies revealed that RBCs, which development is regulated by endogenous and exogenous signals, are biologically viable in the majority of higher plant species. This work reviews the research on RBCs in plant environment interaction and describes the case study of RBCs as a convenient single cell system to study plant responses to Al toxicity.